PERAN PENDIDIKAN DAN PENGAJARAN MORAL BAGI PESERTA DIDIK DALAM RANGKA MENGATASI TAWURAN - Sudarilah, Sudarilah (Jurnal Ilmiah Widya, 2018)
A mass fighting amongst students often happens lately is very troubling and need to be solve gradually and thoroughly. The purpose of this paper is to discuss: (1) the causes and effects of a brawl, (2) education and teaching roles in forming the behavior of students in order to cope with a brawl. The methods used is library studies with descriptive, exploratory approach. It can be concluded that: (1) a brawl may occur due to less of one's personality both because of internal and external factors. A brawl harms not only for the students themselves, but also families and society in general, because it resulted in both in the form of material loss or casualties. (2) the role of moral education at home and school early is crucial to form the personality of the students. It is expected that it may resolve the problem and reduce the losses as well as creating a conducive situation in supporting the smooth national development. It takes an entire society participation in addressing the problem of a brawl, according to the capacity of the respective functions with more emphasis to preventively than of a repressively action.